Correlation of the Single-Assessment Numeric Evaluation (SANE) Score With Hip-Specific Patient-Reported Outcome Measures - Guillaume D. Dumont, M.D., M.B.A; Rachel L. Glenn, M.D; Nicole C. Battle, M.S., A.T.C; Zachary T. Thier, B.S (Elsevier, 2021)
Purpose: The purpose of this study was to determine if the Single-Assessment Numeric Evaluation (SANE) score correlates with existing validated hip-specific patient-reported outcome measures (PROMs), including the Modified Harris Hip Score (mHHS), the International Hip Outcome Tool (IHOT-33), the Hip Outcome Score, Activities of Daily Living subscale (HOS-ADL), and the Hip Outcome Score, Sport-Specific subscale (HOS-SS), for patients preparing to undergo hip arthroscopy for treatment of femoroacetabular impingement syndrome (FAIS). Methods: A single surgeon's operative database was retrospectively reviewed to identify patients undergoing primary hip arthroscopy for treatment of FAIS from April 2018 to October 2019. Patient-specific factors including age, sex, body mass index (BMI), and duration of symptoms were collected. Preoperative SANE, mHHS, IHOT-33, HOS-ADL, and HOS-SS scores were analyzed. Statistical analysis using Pearson correlation was performed to identify the relationship between the SANE score and the mHHS, IHOT-33, HOS-ADL, and HOS-SS, preoperatively. Results: 154 patients were included in the study. The mean mHHS was 54.4 ± 11.7; mean IHOT-33 score was 32.7 ± 15.0; mean HOS-SS 42.9 ± 23.7; and mean HOS-ADL was 63.3 ± 1. The mean SANE score was 36.7 ± 19.9. The Simple Hip Score was directly correlated with the mHHS (P < .01), the IHOT-33 (P < .01); the HOS-ADL (P < .01), and the HOS-SS (P < .01). The mean patient age was 35.9 years; 109 (70.8%) were female and 45 (29.2%) were male. Average patient BMI was 26.9. At the time of patient completion of the questionnaire, the majority of patients (65%) had been having symptoms for >1 year. Conclusion: The SANE score was strongly correlated with mHHS, IHOT-33, HOS-ADL, and HOS-SS in the preoperative setting for patients undergoing hip arthroscopy for treatment of FAIS. Given its simplicity, SANE may be a valuable tool for rapid assessment of joint function and pain in this patient population. Level of Evidence: IV, therapeutic case series.